Heterocyclic flame retardants for rubber based on glycoluril and its derivatives - Salkeyeva, L.K.; Khassenova, G.T.; Röschenthaler, Gerd-Volker; Tayshibekova, Ye.K.; Minayeva, Ye.V.; Zhortarova, А.А.; Sugralina, L.M.; Sagatov, Ye.T.; Salkeyeva, А.K. (KSU publ., 2014)
This article was first proposed to glycoluril and its derivatives as flame retardants for rubbers. The effect of flame retardants on mechanical properties of rubbers was studied. The degree of fire protection was determined. It was shown that the addition of rubber to tetra-N-methylolglycoluril with a synergistic blend of flame retardants had an excellent degree of fire protection in comparison with a series of fire resistant rubbers.
Keywords: flame retardants; glycoluril; tetra-N-chloroglycoluril; tetra-N-methylolglycoluril; vulcanization and scorching